Pengaruh Pengungkapan Corporate Social Responsibility, Persistensi Laba dan Pertumbuhan Laba Terhadap Manajemen Laba Pada Perusaaan Yang Terdaftar di Jakarta Islamic Index - Nawang Kalbuana; Satiti Utami; Aditya Pratama (ITB AAS INDONESIA Surakarta, 2020)
Earning management is often done by the company, but until now very rarely research conducted especially on companies that apply the principle of Islam so that the whole company impressed will apply it. The purpose of this research is to prove and analyze the influence of corporate social responsibility disclosure, profit-statement, and profit growth on earning management, especially in companies listed in the Jakarta Islamic Index (JII) during 2015-2018. Earning management uses Jones ' modification Model (1995), independent variables are researched, among others, corporate social responsibility disclosures, profit persistence, and profit growth. Samples were selected by the Purposive sampling method and were conducted hypothesis testing using multiple linear regression analysis methods. Based on the results of research that has been done proved that in the company applying the ethical principles of Islam shows that the disclosure of corporate responsibility and persistence of profit proved to have no influence on earning management, but profit growth has a significant positive influence on earning management.